Impact of HbA1c levels on coronary SYNTAX score in non-diabetic patients with ST-elevation myocardial infarction undergoing primary angioplasty: A cross-sectional study - Majid Saraei koushki; Razieh parizad; Ali Abdollahzadeh; Ahmad Separham (Caspian Journal of Internal Medicine, 2025)
Background: Glycated hemoglobin A1c (HbA1c) level is related to increased cardiovascular diseases (CVDs) and death, even in non-diabetic subjects. Although in ST-elevation myocardial infarction (STEMI) cases, the association between HbA1c and coronary artery disease (CAD) remains unclear. Methods: This cross-sectional study was conducted on 167 non-diabetic STEMI patients undergoing primary percutaneous coronary intervention (PCI). The SYNTAX score was utilized to evaluate CAD severity. Cases were categorized into three groups based on the HbA1c levels: <5%, 5.1-5.9%, and 6-6.5%. Results: SYNTAX scores significantly increased in the cases with 6 to 6.5 HbA1c levels compared to the other group (28.9±9.5 vs 21.2±5.2 vs 13.7±4.5, P=0.000). Additionally, death was more elevated in this group (4% vs 0% vs 0%, P=0.006). Conclusion: Higher HbA1c levels are strongly associated with coronary atherosclerosis in non-diabetic patients that present with non-diabetic STEMI. Consequently, in non-diabetic STEMI patients, HbA1c may be able to predict the severity of CAD.